2020
DOI: 10.17671/gazibtd.690046
|View full text |Cite
|
Sign up to set email alerts
|

Elmayı en çok kim ısırıyor? Akıllı telefon bağımlılığını etkileyen sosyoekonomik faktörlerin tespiti

Abstract: Bu çalışma akıllı telefon bağımlılığının sosyoekonomik belirleyicilerini araştırmaktadır. Çalışmanın odağı akıllı telefonların konuşma amaçlı kullanımından ziyade artan işlevsellikleri dolayısıyla telefonla konuşma amacı dışındaki (ikincil amaçlar için) kullanımlarıdır. Çalışmanın karakteristik özelliği çalışma kapsamında elde edilen akıllı telefon kullanım sürelerinin doğrudan kullandığı akıllı telefondan temin edilmesidir. Bu bağlamda, çalışma kapsamında, beş hafta boyunca 144 gönüllü katılımcıdan akıllı tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…When smartphone addiction and nomophobia levels were examined in terms of marital status, it was observed that single individuals had higher scores than married individuals, but this data obtained has low statistical power. Considering that smartphone addiction and nomophobia are frequently seen in the young population consisting of students, it can be said that this result is an expected result in line with previous studies (Ankara et al, 2020;Tor Kadıoğlu & Koşar, 2019). When it was examined whether smartphone addiction and nomophobia differed according to educational level, it was observed that there was no difference in terms of nomophobia, and the only difference in terms of smartphone addiction was between undergraduate and graduate levels.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…When smartphone addiction and nomophobia levels were examined in terms of marital status, it was observed that single individuals had higher scores than married individuals, but this data obtained has low statistical power. Considering that smartphone addiction and nomophobia are frequently seen in the young population consisting of students, it can be said that this result is an expected result in line with previous studies (Ankara et al, 2020;Tor Kadıoğlu & Koşar, 2019). When it was examined whether smartphone addiction and nomophobia differed according to educational level, it was observed that there was no difference in terms of nomophobia, and the only difference in terms of smartphone addiction was between undergraduate and graduate levels.…”
Section: Discussionsupporting
confidence: 86%
“…Studies evaluating according to marital status have obtained different results, such as smartphone addiction and nomophobia are more common in single individuals (Nahas et al, 2018;Tor Kadıoğlu & Koşar, 2019), more common in married individuals (Shahrestanaki et al, 2020) or do not differ according to marital status (Alavi et al, 2020;Ertan, 2019). Considering the level of education, it was observed that individuals with bachelor's degree showed significantly more smartphone addiction than individuals with lower or higher education levels (Ankara et al, 2020;Shahrestanaki et al, 2020). However, there are also studies indicating that smartphone addiction and nomophobia do not differ in terms of educational level (Alavi et al, 2020;Gezgin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Nigeria on this subject, it was reported that the presence of a chronic disease affected sleep quality poorly, 28 while in some studies conducted in our country, it was found that chronic diseases decreased sleep quality. 29, 30 Ankara et al 31 conducted a study with 144 participants and found that there was no significant difference between employees and non-employees in terms of SPAS.…”
Section: Discussionmentioning
confidence: 99%